Muzaro'ah dan Aplikasinya Pada Perbankan Syari'ah - Afrik Yunari (LPPM IAI Hasanuddin Pare-Kediri, 2016)
Land is important in the agricultural sector. Islamic teachings suggest that if a person has land, then he must utilize and cultivate it. The cultivation of agricultural land can be done in various ways as has been taught by Islam as well as by way of self-processed by those who have or by way of lending to others to work on. In this case, Islam has a solution of agricultural land use with a system that more shows the values ​​of justice for both parties, namely by sharing profit sharing system using muzara'ah system. This system in syariah bank can be applied as one of financing in agriculture sector. However, in reality the financing of muzara'ah in syar’i banking is still very minimal because from the point of view of the banking sector itself is less attractive to invest. Therefore, this paper will discuss about muzara'ah and its application to syar’i banking.